The efforts of the students’ discipline in improving learning quality - Eti Hikmawati (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
This research aimed to find the efforts of the students discipline in improving learning quality at MAN Tegalrejo and MAN 1 Magelang. The method used is descriptive qualitative. The results of this study showed that: First, the efforts undertaken in MAN Tegalrejo by disciplining learners to obey the Madrasa discipline and the readiness of the program and its implementation. Second, the efforts at MAN 1 Magelang through academic discipline by fulfilling the rights and obligations of learners, during the activities in the Madrasa, activities of class and group management, and the completeness of classroom infrastructure. In addition, hidden discipline was also applied, which was discipline in carrying out extracurricular activities and Punishment. Third, supporting factors in MAN Tegalrejo were: The existence of discipline when learning and outside of learning time both academic and non-academic activities, the readiness of learning program learners through three stage (preparation stage, ongoing stage, and evaluation stage). While in MAN 1 Magelang namely: the existence of facilities, cooperation between BK (counseling guidance) with homeroom teacher in problem solving, harmonious relationship between the teacher-students, teachers-other Madrasa members, giving awards and scholarship for outstanding students, and monitor their activities by cooperation of Madrasa-parents.